Daily field checking list by Walter Rosene, December 13, 1936 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Bird checklist dated December 13, 1936. This checklist was used by Walter Rosene to record birds sighted around the Beaver Creek Iron Bridge with Bob Walker between 8:30 and 11:30. Plustek--flatbed